2016
DOI: 10.1016/j.ophtha.2015.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Atopic Keratoconjunctivitis in Children: Clinical Features and Diagnosis

Abstract: International audienceno abstrac

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 7 publications
1
17
0
4
Order By: Relevance
“…Brémond-Gignac reported the largest series of pediatric AKC, which included 23 patients. 12 Most clinical features in that case series overlapped with those of VKC, 12 as documented in our case. The presence of AKC-related clinical features but an absence of VKC-related clinical features in combination with a history of eczema and conjunctivitis and/or keratitis may secure an accurate diagnosis of AKC in children.…”
Section: Figuresupporting
confidence: 71%
See 2 more Smart Citations
“…Brémond-Gignac reported the largest series of pediatric AKC, which included 23 patients. 12 Most clinical features in that case series overlapped with those of VKC, 12 as documented in our case. The presence of AKC-related clinical features but an absence of VKC-related clinical features in combination with a history of eczema and conjunctivitis and/or keratitis may secure an accurate diagnosis of AKC in children.…”
Section: Figuresupporting
confidence: 71%
“…11 In 2015, Brémond-Gignac proposed the diagnostic criterion of pediatric AKC as the presence of severe allergic conjunctivitis with AD that is diagnosed before 16 years of age. 12 VKC is another rare but severe type of allergic conjunctivitis that may involve the cornea. Severe itching and cobblestone papillae are the most significant characteristics of VKC, and thus have diagnostic value.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…A French study concluded that all young, allergic boys with eye-rubbing tendencies and a recent onset of corneal astigmatism should be examined regularly in order for keratoconus to be detected at an early stage [64]. Studies demonstrating the relationship between AD and cataract in young individuals have also been published [65,66].The most frequent symptoms of AKC in paedi-atric patients with atopy are conjunctival hyperemia and eczema (96%) [67].…”
Section: Childrenmentioning
confidence: 99%
“…A CCA tem inicio tradicionalmente no final da adolescência e inicio da vida adulta, (51) embora tenham sido descritos vários casos em crianças. (52) Entre as demais conjuntivites alérgicas, a CCA tem maior gravidade pois acomete progressivamente a conjuntiva e a córnea dos pacientes, podendo persistir por toda a vida, representando uma potencial causa de cegueira nesse grupo. (37)…”
Section: Introductionunclassified